Document Smart The a-To-Z Guide to Better Nursing Documentation. - Capriotti, Theresa (Wolters Kluwer, 2019)
"Handbook detailing exactly what to document in any situation for nurses in all practice settings. Over 300 alphabetically organized topics cover diseases, emergencies, procedures, legal and ethical problems, and difficult situations involving patients, families and other health care professionals. Legal casebook"--